Analysis Of Buying Interest In Online Products Of Islamic University Students In Malang District - Lestari, Rr.Hesti Setyodyah; Fitrianingsih, Defit; Sinollah, Sinollah; Ramdhan, Tri Wahyudi (ITB AAS INDONESIA Surakarta, 2024)
The purpose of this study was to determine the characteristics of students in Malang in shopping both online and their influence on the movement of purchasing behavior of students in Malang to make purchases online. The research technique uses quantitative descriptive research. The sample amounted to 400 students. Data collection techniques through questionnaires. Regarding the analysis of test results with PLS support. The results showed that the purchase intention variable was influenced by the variables of trust, discount and promotion by the seller. In addition, the level of public trust in online shopping websites with a good reputation and having a variety of product variations is one of the things that attracts buyer interest. Based on the results of PLS analysis, it is known that online shopping behavior can reduce students' shopping movements, especially on food / beverage needs, children's needs and toys, cosmetics and skin care, and tertiary fashion.